Spontaneous Fermentation of Regional Fruit Beverages using Buffalo Yogurt Whey - Rebak, Gladis Isabel; Cantero, Ramona Victoria; Elizabeth Obregón, Gladys Roxana (Journal of Buffalo Science, 2025)
Yogurt whey is a by-product of the filtration process in Greek-style buffalo yogurt. It contains beneficial compounds such as proteins, minerals, carbohydrates, and lactic acid bacteria; yet, it is often discarded, contributing to environmental contamination due to its high biological oxygen demand. This study aimed to valorize this by-product by developing fermented beverages formulated by combining yogurt whey with regional citrus and tropical fruits. Eighteen formulations were prepared using whey, fruit pulp or juice (grapefruit and passion fruit), sugar, and filtered water, followed by spontaneous fermentation for 48 hours at ambient temperature (25 ± 2 °C). Physicochemical parameters (pH, °Brix, and Density) were measured before and after the filtration process. Two formulations, grapefruit (citrus group) and passion fruit (tropical group), were selected for sensory evaluation by 30 untrained panelists, who used a 9-point hedonic scale to assess aroma, flavor, and color. Physicochemical results showed minor changes in pH and significant increases in °Brix and Density in samples after filtration, particularly in beverages made with tropical fruits. Sensory analysis revealed high overall acceptability; passion fruit beverages received significantly higher overall and flavor scores from female participants than from males (p = 0.043). The results demonstrate the feasibility of transforming buffalo yogurt whey into a regionally inspired fermented functional beverage with favorable sensory acceptance and commercial potential. This approach presents an innovative strategy for reducing waste in the dairy industry. It supports sustainable food systems through the valorization of underutilized by-products and local fruits, which aligns with the principles of the circular economy.